INHIBITOR OF SYNTHESIS OF TUMOR NECROSIS FACTOR-Α, PENTOXIFYLLINE, IN COMBINED THERAPY OF THE CHRONIC HEART FAILURE - O. P. Dudarenko; E. L. Shkol'nik (Столичная издательская компания, 2016)
Aim. To study effects of pentoxifylline in combination with basic therapy on functional status, intracardiac hemodynamics, neurohormones and proinflammatory cytokines levels in patients with chronic heart failure (CHF) complicated ischemic heart disease (IHD).Material and methods. 55 patients with CHF complicated IHD (83,6% men and 16,4% women) were involved in the study. Duration CHF was 2,4 years in average. Class I of CHF (NYHA) was registered in 5 patients (9,1 %), class II - in 33 patients (60,0 %), class III - in 16 patients (29,1 %), class IV in 1 patient (1,8 %). Dynamics of life quality, severity of clinical status, functional reserve, intracardiac hemodynamics, neurohormones and proinflammatory cytokines levels was assessed during 9 months of therapy.Results. Pentoxifylline, added to standard therapy of CHF, resulted in improvement of life quality, intracardiac hemodynamics and clinical status of the patients with CHF of I-II class (NYHA). Besides reduction in proinflammatory cytokine (tumor necrosis factor-α, interleukin-6) and neuronhormone levels was found in patients with CHF of I-II class.Conclusion. Pentoxifylline can be useful in combined therapy of CHF